A Phonological Analysis of English Brand Name Pronunciations by Indonesian, Japanese, and Korean Speakers: A Study of World Englishes - Maldini, Rossy; Kinanditya, Agata Pritha; Amelia, Anita; Darsih, Endang (Proceedings Series on Social Sciences & Humanities, 2025)
The purpose of this study is to analyze the phonological adaptation patterns in the pronunciation of English brand names by native speakers of Indonesian, Japanese, and Korean. This study distinct from the phenomenon of globalization and the expantion of international brands, which provide phonological issues, Particulary when foreign words must be adapted to the phonological system of the mother tongue (L1). by Using a qualitative approach and descriptive phonological analysis, the data were collected from the pronunciation of famous brands by speakers from the three language groups. The findings indicate that segmental and suprasegmental adaptations are heavily influenced by the phonotactic structure of each L1. Japanese and Korean speakers typically use epenthesis and simplify segments to maintain the dominant CV syllable structure, whereas Indonesian speakers are more flexsible and frequently to keep the original sounds Furthermore, stress and intonation in speech show changes that match L1 prosody patterns. Sociolinguistic factors such as brand proximity also influence the level of adaption. This research increases the understanding of pronunciation variance in the context of World Englishes and gives implications for foreign language pronunciation education as well as interlingual phonology studies.